(untitled) (Bangladesh Journal of Plant Taxonomy, 2017)
A new species Oberonia jhae Chowlu et Rab (Orchidaceae) is described and illustrated from India. This species is allied to Oberonia emarginata King & Pantl, but differs from it in plant height, densely flowered inflorescences, ovate and entire sepals and very short column and lanceolate, acute petals. Keywords: Arunachal Pradesh; India; Oberonia; New Species; Orchids. Bangladesh J. Plant Taxon. 24(1): 4952, 2017 (June)